1997
DOI: 10.1002/(sici)1097-4628(19970705)65:1<155::aid-app19>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dyeability and morphology of cotton fiber subjected to cellulase treatment

Abstract: Unprocessed and mercerized cotton fibers were treated with commercial crude cellulase. The changes in the dyeability and structural features of the fiber due to cellulase treatment were studied. The dyeability was examined in terms of uptake of three reactive dyes and the apparent affinity of Congo Red to cotton fiber. The dyeability of the unprocessed fiber was assumed to be influenced by some impurities present in it. This fiber probably resembled polynosic fiber in molecular aggregate at a certain stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This means that a reduction in the fin ness of the cotton fibers takes place due to enzymat hydrolysis. Our work also suggested that enzymat hydrolysis occurs in the secondary wall of the cottf fibers, even during the initial step of hydrolysis, due ie coexistence of molecular disaggregating enzymes i the cellulase [4]. ' Polyester fabrics treated with an aqueous sodium hyroxide solution, also associated with a reduction in ibric weight, have a silky handle.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…This means that a reduction in the fin ness of the cotton fibers takes place due to enzymat hydrolysis. Our work also suggested that enzymat hydrolysis occurs in the secondary wall of the cottf fibers, even during the initial step of hydrolysis, due ie coexistence of molecular disaggregating enzymes i the cellulase [4]. ' Polyester fabrics treated with an aqueous sodium hyroxide solution, also associated with a reduction in ibric weight, have a silky handle.…”
mentioning
confidence: 58%
“…We ave selected KES to measure the bending and shear roperties of cotton fabrics after the same cellulase treatient we reported on previously [4].…”
mentioning
confidence: 99%
“…It was noted that the parameters of bending and shear properties decreased for all cotton fabrics tested. The reduction [2] in fiber fineness induced by cellulase treatment decreased the friction force between fibers, and improved the recovery from bending and shear deformations. The reduction of fiber fineness reasonably decreased not only the elastic parameters of B and G, but also the inelastic parameters of 2HB, 2HG and 2HG5.…”
Section: Changes In Cotton Fabric Propertiesmentioning
confidence: 99%
“…Previously, we reported that the dyeability [1,2] and crystallinity [2] of cotton fibers changed even in the first step of cellulase treatment. Observation using a scanning electron microscope [2] revealed that the cellulase treatment decreased fiber fineness by eliminating the primary layer, resulting in a material weight loss of approximately 5% [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation